Nature Morte ?? : Tentoonstellingsproject rond Kunst en Ecologie. - Cultureel Centrum Leuven; Baetens, Jan; Baker, Carole; Börocz, Zsuzsanna; Cooreman, Els; De Vlieghere, Dieter; Desseaux, Stefan; Devlies, Carl; Donders, Frisia; Dossche, Caroline; Echelpoels, Leen; Fabre, Jan; et al. (Leuven : Cultureel Centrum Leuven, 1997)
Bernier, Pascal ; Bijl, Guillaume ; Bisschop, Geert ; Bult, Annet ; Buyse, Kristien ; Casaer, Paul ; Crabeels, Cel ; De Beul, Bert ; de Gruyter, Voebe ; Deleu, Luc ; Delrue, Ronny ; Denmark ; Dera, Cor ; Wesselli, Wessel Di ; Dossche, Caroline ; Fabre, Jan ; Fastenaekens, Gilbert ; Jodogne, Lucas ; Kempenaers, Jan ; Kooijmans, Jeroen ; Körmeling, John ; Lemmen, Hans ; Lindemans, Gorik ; Luyten, Mark ; Massart, Jean-Georges ; Panamarenko ; Servaas ; Tuymans, Luc ; van Biesen, Stefaan ; Van Caeckenbergh, Patrick ; Ham, Peter Van Der ; Vanderleenen, Marc ; Vanhemelryck, Kris ; Verschueren, Bob ; Vos, Jan ; Wastijn & Deschuymer
biografie
Nature Morte??, Cultureel Centrum Leuven, 13.04 - 23.05.1997
Engels
Frans
Nederlands
boek